Pendampingan Penanaman Nilai Moral Spritual melalui film Animasi Kisah Nabi di Pojok Literasi Kampung Pasir - Thohal Arobi; Solihah Bagus; Usep Setiawan; Didih Ahmadiah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This community service program aims to provide assistance in instilling moral and spiritual values through animated films about the stories of the Prophets at the Literacy Corner of Kampung Pasir. Moral and spiritual education is a fundamental aspect of character building, especially for children, who are in a critical stage of personal and social development. However, the rapid development of technology and the dominance of entertainment-oriented media have reduced children’s exposure to educational content that emphasizes moral and spiritual values. Therefore, innovative and engaging learning media are needed to support character education within the community.This program employed a descriptive qualitative approach to describe the implementation process and outcomes of the mentoring activities. The participants were elementary school–aged children who actively joined activities at the Literacy Corner of Kampung Pasir. Data were collected through observation, interviews, and documentation during the mentoring sessions. The activities were conducted by screening animated films depicting the stories of the Prophets, followed by guided discussions and reflections to help children understand and internalize the moral and spiritual values conveyed in the films.The results indicate that the use of animated films about the stories of the Prophets effectively attracted children’s interest and enhanced their engagement in learning activities. The children demonstrated an improved understanding of moral and spiritual values such as honesty, patience, empathy, obedience to God, and mutual respect. Furthermore, positive changes in attitudes and behaviors were observed, including increased discipline, respect for others, and the ability to apply the values learned in their daily lives. The mentoring activities also strengthened the role of the Literacy Corner as a non-formal learning space that supports character education within the community.In conclusion, mentoring activities using animated films about the stories of the Prophets can be an effective approach to fostering moral and spiritual values among children in community-based literacy programs. Continuous implementation and collaboration among stakeholders are recommended to ensure the sustainability and long-term impact of character education initiatives.